Janzen–Connell patterns can be induced by fungal‐driven decomposition and offset by ectomycorrhizal fungi accumulated under a closely related canopy. (6th November 2017) - Deniau, Maud; Jung, Vincent; Le Lann, Cécile; Kellner, Harald; Béchade, Benoît; Morra, Thibault; Prinzing, Andreas
Abstract: Seedlings near a conspecific adult might suffer increased mortality due to pressure from enemies such as below‐ground pathogenic fungi (Janzen–Connell hypothesis), however, variation exists among taxa such that some experience low levels of mortality. We hypothesized that seedlings close to adults might profit, rather than suffer, from below‐ground fungi, notably from mycorrhiza or decomposers, in particular near large adult trees and under a closely related canopy. We planted oak seedlings in a temperate forest at different distances from adults and followed seedling mortality, budburst (early budburst permitting photosynthesis during the best light conditions) and leaf herbivory. We applied fungicide on half of the seedlings for 2 years to identify the net effect of below‐ground fungi on seedlings. We quantified seedling mycorrhization and fungal‐driven decomposition of a neighbourhood‐specific and an unspecific substrate, local oak leaves and cellulose respectively. Finally, we related mycorrhization and decomposition to seedling performance. We found that, in seedlings planted close to conspecific adults, below‐ground fungi had a negative net effect on seedlings: elimination of fungi, surprisingly, decreased herbivory. This effect could be due to oak leaf decomposition, which was related to increased seedling herbivory and was higher near a conspecific adult. Under a closely related canopy, however, the net effect of below‐ground fungi on nearby seedlings became positive: elimination of fungi delayed budburst. This effect could be due to colonization by the ectomycorrhizal fungus Cortinarius sp., which related to accelerated budburst and was higher near a conspecific under a closely related canopy. Effects of below‐ground fungi on nearby seedlings were not dependent on the size of the conspecific and were species but not lineage specific. Overall, our results suggest that a Janzen–Connell‐like pattern, that is, increased mortality of seedlings near conspecific adult, can be (1) induced by specialist decomposers increasing the nutritional quality of conspecific seedlings to herbivores, and (2) offset by ectomycorrhizal fungal mutualists under a closely related canopy. Coexistence among closely related adult trees appears to change interactions between adults and nearby conspecific seedlings from conspecific inhibition to conspecific facilitation. A plain language summary is available for this article. Abstract : Plain Language Summary